2018
DOI: 10.1016/j.mmcr.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution patterns of Fonsecaea agents of chromoblastomycosis, exemplified by the first case due to F. monophora from Argentina

Abstract: Chromoblastomycosis is a mutilating infection of the skin and subcutaneous tissues caused by melanized fungi belonging to the order Chaetothyriales. Proven cases of the main agent, Fonsecaea pedrosoi are mainly limited to (sub)tropical, humid climates of Latin and Central America and the Caribbean. Fonsecaea monophora has a global distribution along the equator. Cases outside the (sub)tropics have thus far mostly been considered to have been imported, but here we report the first endemic case by F. monophora f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Several published articles lacked detailed records about patients' residencies, resulting in difficulty in determining the environmental source of pathogens. According to epidemiological evidence, some researchers found that F. monophora had a broad distribution, implying its habitats were more varied [8]. Our patient never left northern China and was most likely infected locally.…”
Section: Discussionmentioning
confidence: 65%
“…Several published articles lacked detailed records about patients' residencies, resulting in difficulty in determining the environmental source of pathogens. According to epidemiological evidence, some researchers found that F. monophora had a broad distribution, implying its habitats were more varied [8]. Our patient never left northern China and was most likely infected locally.…”
Section: Discussionmentioning
confidence: 65%
“…In mehreren veröffentlichten Artikeln fehlten detaillierte Aufzeichnungen ĂŒber die Wohnorte der Patienten, was die Bestimmung der Erregerquelle erschwerte. Nach epidemiologischen Erkenntnissen stellten einige Forscher fest, dass F. monophora weit verbreitet ist, seine LebensrĂ€ume also vielfĂ€ltig sind [8]. Unser Patient hat Nordchina nie verlassen und wurde höchstwahrscheinlich lokal infiziert.…”
Section: Weitere Mikrobiologische Untersuchungenunclassified
“…Chromoblastomycosis caused by Fonsecaea spp. has been reported in countries including Argentina (Label et al, 2018), Venezuela (Paniz-mondol et al, 2008), Peru (Schwalb & Seas, 2020), China (Bao et al, 2018;You et al, 2019;Zhang et al, 2019;Shen et al, 2020;Chen et al, 2021), India (Varghese et al, 2016), the United States (Takei et al, 2007), Mexico (Carolina et al, 2015), Canada (Mourad & Haber, 2020), and Cuba (Badali et al, 2013). Molecular phylogenetic analyses have shown that several sibling species are involved.…”
Section: Introductionmentioning
confidence: 97%